Modulation of membrane transporter expression and activity by mangiferin, epigallocatechin-3-gallate (EGCG), quercetin, and kaempferol: A review - Nazihah, Maryam; Estuningtyas, Ari (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Membrane transporters are one of the important factors in drug pharmacokinetics. These proteins mediate drug transport in and out of cells; efflux transporters export the drug from inside the cell, while influx transporters facilitate the entry of it into the cell. Thus, the presence of these membrane proteins influences drug levels in cells, which then determines the drug efficacy and safety profile. Many studies have shown that various exogenous compounds can modulate the activity and/or expression of membrane transporters, including bioactive molecules. Flavonoids are secondary plant metabolites that are very abundant and widely used in diets, supplement products, and traditional medicine. Apart from their medical benefits, flavonoids have been reported to interact with membrane transporters involved in drug absorption and drug resistance. These interactions can be beneficial in multidrug resistance conditions or awareness of drug toxicity. This article collects studies that have been conducted on four widely consumed plant-derived compounds: mangiferin, epigallocatechin-3-gallate (EGCG), quercetin, and kaempferol, and their effects on membrane transporters. The effects can be a consideration when administering these flavonoids together with medication.